Automa????o de testes para aplica????es m??veis como servi??o Automated Mobile Testing as a service AM-TaaS - Rojas, Isabel Karina Villanes (2016)
Submitted by Divis??o de Documenta????o/BC Biblioteca Central (ddbc@ufam.edu.br) on 2016-12-15T18:14:06Z No. of bitstreams: 1 Disserta????o - Isabel K. V. Rojas.pdf: 4369495 bytes, checksum: 92fd0a46d83a7bace55dd126266a19c4 (MD5)